SmartBreastfeed: Effectiveness of a Digital Intervention in Reducing Postpartum Fatigue and Enhancing Breastfeeding Motivation - Lia Idealistiana; Achmad Fauzi; Astri Mutiar; Linlin Lindayani; Irma Darmawati (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2025)
Background: Postpartum fatigue is a highly prevalent condition affecting up to 88% of mothers in the early postpartum period, negatively influencing maternal well-being and breastfeeding outcomes. In Indonesia, fatigue contributes to low exclusive breastfeeding rates, which remain below national and WHO targets. Digital health solutions offer promising opportunities to provide continuous breastfeeding support; however, existing applications are predominantly infant-focused and rarely address maternal psychosocial needs such as fatigue and motivation. Objective: To evaluate the effectiveness of the SmartBreastfeed mobile application in reducing postpartum fatigue and enhancing breastfeeding motivation among mothers during the first six weeks after childbirth. Methods: A quasi-experimental pretest–posttest control group design was employed among 64 postpartum mothers recruited from two urban health facilities. Participants were assigned to either the intervention group using SmartBreastfeed for four weeks or the control group receiving standard education through leaflets. Postpartum fatigue and breastfeeding motivation were assessed using validated Indonesian versions of the Postpartum Fatigue Scale (PFS) and Breastfeeding Motivation Scale (BFMS). Data were analyzed using paired t-tests and ANCOVA with significance set at p < 0.05. Results: Mothers using SmartBreastfeed experienced a significantly greater reduction in fatigue scores compared with controls (Δ = -13.5 ± 5.2 vs. -4.1 ± 3.8; p < 0.001). The intervention group also demonstrated significant improvements in breastfeeding motivation—including increased intrinsic (p < 0.001) and extrinsic motivation (p = 0.02), and reduced amotivation (p = 0.01). ANCOVA showed the intervention as the strongest predictor for improved outcomes, with medium-to-large effects (partial η² = 0.09–0.27). Conclusion: SmartBreastfeed effectively reduced postpartum fatigue and enhanced breastfeeding motivation through personalized digital support integrating self-monitoring, educational modules, reminders, and motivational messaging. This user-centered innovation shows potential to complement community maternal health programs and improve breastfeeding success in Indonesia